Autologous dendritic cells loaded with antigens from self-renewing autologous tumor cells as patient-specific therapeutic cancer vaccines - Robert O. Dillman; Gabriel I. Nistor; Hans S. Keirstead (Taylor & Francis Group, 2023)
A promising personal immunotherapy is autologous dendritic cells (DC) loaded ex vivo with autologous tumor antigens (ATA) derived from self-renewing autologous cancer cells. DC-ATA are suspended in granulocyte-macrophage colony stimulating factor at the time of each subcutaneous injection. Previously, irradiated autologous tumor cell vaccines have produced encouraging results in 150 cancer patients, but the DC-ATA vaccine demonstrated superiority in single-arm and randomized trials in metastatic melanoma. DC-ATA have been injected into more than 200 patients with melanoma, glioblastoma, and ovarian, hepatocellular, and renal cell cancers. Key observations include: [1] greater than 95% success rates for tumor cell cultures and monocyte collection for dendritic cell production; [2] injections are well-tolerated; [3] the immune response is rapid and includes primarily TH1/TH17 cellular responses; [4] efficacy has been suggested by delayed but durable complete tumor regressions in patients with measurable disease, by progression-free survival in glioblastoma, and by overall survival in melanoma.